The experience of COVID-19: assessing the Malaysian counselors in training coping strategies - Abdullah, Siti Salina; Arifin, Suhaili; Ramley, Fazliyaton; Md Shah, Kamarul; Yusop, Yusni Mohamad; Ahamad, Masturina; Mat Najib, Norazizalina (International Journal of Public Health Science (IJPHS), 2025)
The COVID-19 pandemic also had a psychological impact on various levels of society including trainee counselors. Therefore, the aim of this study is to explore the coping strategies employed by trainee counselors to overcome their challenges within their internship during COVID-19. This study is a quantitative study and was conducted among 106 final-year trainee counselors enrolled in a bachelor's counseling program at the University Malaysia Terengganu (UMT). There were two instruments used in this study, consisting of a sociodemographic questionnaire and the Malay Brief COPE (MBC) scale. The findings indicate that emotion-focused is mostly used by counselors in training with a mean value of 28.96 (SD=4.891); the mean of problem-focused was 18.08 (SD=3.080); and the mean of avoidance coping was 26.12 (SD=5.341). The study's dataset can be used by counselor educators, the Malaysian Board of Counsellors, clinicians, and academicians to improve the effectiveness and competencies of trainee counselors completing internship during the adverse period.